Aurocyanide Adsorption onto Granular Activated Carbon Impregnated with Sds Anionic Surfactant - Navarro-Donoso, P; Vargas-Riquelme, C (Springer Science and Business Media Deutschland GmbH, 2022)
The impregnation of granular activated carbon with the anionic surfactant sodium dodecylsulfate (SDS) was studied and the influence on aurocyanide adsorption was evaluated. Thermodynamic and kinetic parameters were also determined. The impregnation of activated carbon with SDS improves gold adsorption by 10%, showing a cleansing effect on the carbon surface which was displayed in a higher specific surface area. Specific pore volume and average pore diameter did not undergo important changes. Increasing the temperature decreases gold adsorption on modified carbon. The standard enthalpy of adsorption and the activation energy were calculated, getting values of − 41.3 kJ/mol and 15.0 kJ/mol, respectively. © 2022, The Author(s).